2021
DOI: 10.3390/nano11020344
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Carrier Extraction Processes in GaSb/AlGaAs Quantum Nanostructure Intermediate-Band Solar Cells

Abstract: From the viewpoint of band engineering, the use of GaSb quantum nanostructures is expected to lead to highly efficient intermediate-band solar cells (IBSCs). In IBSCs, current generation via two-step optical excitations through the intermediate band is the key to the operating principle. This mechanism requires the formation of a strong quantum confinement structure. Therefore, we focused on the material system with GaSb quantum nanostructures embedded in AlGaAs layers. However, studies involving crystal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Further investigations were focused on the SAQD formation in III–V heterosystems with a higher E loc value. This trend has involved such well-known SAQDs system as GaSb/GaAs [ 19 , 20 , 21 ] and relatively novel heterosystems, for instance, GaSb/AlGaAs [ 22 , 23 ], GaSb/AlAs [ 24 ], InSb/AlAs [ 25 ], InGaAs/GaP [ 26 , 27 ], GaSb/GaP [ 28 , 29 ], InGaSb/GaP [ 30 , 31 ] and others, as discussed in [ 32 ]. The highest E loc value was obtained for GaSbP/GaP SAQDs (about 1.18 eV [ 29 ]), and it results in a storage time of about four days.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations were focused on the SAQD formation in III–V heterosystems with a higher E loc value. This trend has involved such well-known SAQDs system as GaSb/GaAs [ 19 , 20 , 21 ] and relatively novel heterosystems, for instance, GaSb/AlGaAs [ 22 , 23 ], GaSb/AlAs [ 24 ], InSb/AlAs [ 25 ], InGaAs/GaP [ 26 , 27 ], GaSb/GaP [ 28 , 29 ], InGaSb/GaP [ 30 , 31 ] and others, as discussed in [ 32 ]. The highest E loc value was obtained for GaSbP/GaP SAQDs (about 1.18 eV [ 29 ]), and it results in a storage time of about four days.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing an intermediate energy band (IB) makes it possible to increase the absorption coefficient and the short-circuit current density J sc without decreasing the open-circuit voltage V oc . [6][7][8][9] GaAsPN materials have attracted much recent research attention; this alloy can be grown with an alterable bandgap staying lattice matched to Si. [10][11][12][13] These properties make this alloy a promising material for the manufacturing of quantum wells (QWs) and quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] These properties make this alloy a promising material for the manufacturing of quantum wells (QWs) and quantum dots (QDs). [14][15][16] Shoji et al 9 confirmed that GaSb QDs and quantum rings (QRs) can be shaped on AlGaAs layers by Stranski-Krastanov growth and Assoaking techniques. They also investigated the suitability of multilayer quantum dot solar cells (QDSCs) for use in IBSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiang Zhang, Shengwen Hou and Chaoyang Li of Kochi University of Technology, Japan presented “Titanium Dioxide-Coated Zinc Oxide Nanorods as an Efficient Photoelectrode in Dye-Sensitized Solar Cells” [ 4 ]. Yasushi Shoji, Ryo Tamaki and Yoshitaka Okada of National Institute of Advanced Industrial Science and Technology, Japan and The University of Tokyo, Japan presented “Temperature Dependence of Carrier Extraction Processes in GaSb/AlGaAs Quantum Nanostructure Intermediate-Band Solar Cells” [ 5 ]. Panus Sundarapura, Xiao-Mei Zhang, Ryoji Yogai, Kazuki Murakami, Alain Fave and Manabu Ihara of Tokyo Institute of Technology, Japan and Univ Lyon, France presented “Nanostructure of Porous Si and Anodic SiO 2 Surface Passivation for Improved Efficiency Porous Si Solar Cells” [ 6 ].…”
mentioning
confidence: 99%